INOVASI PERMAINAN GYMBALL DALAM PEMBELAJARAN PJOK UNTUK MENINGKATKAN MOTIVASI BELAJAR MURID - Agustiawan Emadeju, Jhoni; Nur Muhammad, Heryanto; Priambodo, Anung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical Education, Sports, and Health (PJOK) plays a crucial role in developing students’ physical fitness, motor skills, and socio-moral values through structured physical activities; however, recent studies indicate a decline in students’ learning motivation, particularly in contexts where instructional approaches remain conventional and insufficiently innovative. This study aimed to examine the effect of gymball game innovation in PJOK learning on students’ learning motivation. A quantitative approach with a quasi-experimental one-group pretest–posttest design was employed. The population consisted of 360 tenth-grade students from public senior high schools in Jombang, Indonesia, with 72 participants selected through purposive sampling. Data were collected using a validated Likert-scale motivation questionnaire adapted to the physical education context and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test due to the ordinal nature of the data. Results indicated an increase in motivation scores following the intervention, with the median improving from 63 to 72, and statistical testing confirming a significant difference between pretest and posttest scores (Z = −6.214, p < 0.05) with a large effect size (r = 0.73). These findings suggest that gymball-based learning innovation positively influences student motivation in PJOK classes. The study highlights the importance of integrating creative and interactive physical learning media to foster engagement and intrinsic motivation, contributing conceptually and practically to the advancement of student-centered physical education pedagogy.